Investigation of the photoinitiation of methyl methacrylate polymerization by 2-morpholino acetonaphthone - Keskin, Sevnur; Arsu, Nergis (ELSEVIER SCIENCE SA, 2006)
2-Morpholino acetonaphthone (MPM) was synthesized as a cleavable photoinitiator and the structure of the photoinitiator was confirmed by spectral and elemental analysis. The photoinitiation capability of MPM was demonstrated by using methyl methacrylate and a formulation containing multifunctional monomers. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: 2-morpholino acetonaphthone; photoinitiator; photoinduced polymerization; RT-FTIR; Chemistry; Materials Science